Social Media Network Analysis (SNA): Identifikasi Komunikasi dan Penyebaran Informasi Melalui Media Sosial Twitter - Novia Amirah Azmi; Aqil Teguh Fathani; Delila Putri Sadayi; Ismi Fitriani; Muhammad Rayhan Adiyaksa (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
This article aims to identify the level of communication, information dissemination, and the dominant status of online media in Indonesia in disseminating information about COVID-19 circulating to the public, especially Twitter users. Qualitative research methods are used in this study to describe the findings obtained from Social Network Analysis on national online media. They are Twitter accounts @CNN Indonesia, @Detikcom, @KompasTV, and @VIVAcoid, and see the intensity of the interaction using #lawancovid and #saatnyaNyalakanTandaBahaya. The analysis was carried out using NVivo 12+ software in looking for graphs, interactions, and network intensity which were grouped into recipient actors, namely government, non-government organizations (NGOs), and the community, and saw the level of Centrality in SNA, which consisted of degree centrality, betweenness centrality, and closeness centrality regarding the spread of COVID-19. The study results stated: (1) the dissemination of information through Twitter media carried out by the national media became dominant and became a prominent tagline in the news summary during June 2021. (2) the highest recipients of information and responses were the public with an average of (0.574), NGOs (0.228), and government (0.2). (3) community interaction patterns and responses related to COVDI-19 also increased compared to other news taglines. (5) A good centrality measurement result is the @KompasTV account, with a degree centrality value of 63, closeness centrality 0.016, and betweenness centrality 3906.000. (6) for the overall framing carried out by the media, it is increasingly making people afraid to do activities outside the home to increase awareness in suppressing the spread of COVID-19 in Indonesia